Autologous micrografts and methotrexate in plantar erosive lichen planus: healing and pain control. A case report. Issue 1 (1st January 2020) - Miotti, G.; Zingaretti, N.; Guarneri, G. F.; Manfrè, V.; Errichetti, E.; Stinco, G.; Parodi, P. C.
Abstract: Erosive lichen planus is an uncommon variant of lichen planus. We report a case of longstanding and refractory plantar ELPs causing disabling and opiate-resistant pain treated with 'classic' meshed skin graft combined with Rigenera ® micrografts. After approximately 9 months follow-up, no clinical recurrence or pain were observed. Erosive lichen planus (ELP) is an uncommon variant of lichen planus, involving oral cavity and genitalia and, less often plantar areas, where it usually presents with chronic erosions of the soles, along with intense, disabling pain and progressive loss of toenails. An abnormal immune cellular response (CD8+ lymphocytes and macrophages) and the consequent altered production of multiple mediators (interleukin-12, interferon-γ, tumor necrosis factor-α, RANTES and MMP-9), seem to play a crucial role in the pathogenesis, although the etiology remains uncertain. From a histological point of view, ELP shows keratinocyte apoptosis, intense inflammatory response and basal epithelial keratinocytes TNF-α overexpression. Several therapies have been proposed, with variable and controversial results. While topical corticosteroids and topical calcineurin inhibitors are the treatments of choice for localized forms, short pulses of systemic glucocorticoids, phototherapy, and systemic immunosuppressants are recommended for generalized cases. Surgery has been reported as a possible therapeutic option in refractory and stable cases with localized lesions, either alone or with cyclosporine. Herein, we report a case of longstanding and refractory plantar ELPS causing disabling and opiate-resistant pain treated with 'classic' meshed skin graft combined with Rigenera® micrografts.